Subaxial Cervical Spine Injuries: WFNS Spine Committee Recommendations - Sharif, S (2020)
To formulate specific guidelines for the recommendation of subaxial cervical spine injuries concerning classification, management, posttraumatic locked facets and vertebral artery injury. Computerized literature was searched on PubMed and google scholar database from 2009 to 2020. For classification, keywords "Sub Axial Cervical Spine Classification," resulting in 22 articles related to subaxial cervical spine injury classification system (SLICS) system and 11 articles related to AO (Arbeitsgemeinschaft für Osteosynthesefragen, German for "Association for the Study of Internal Fixation") Spine system. The literature search yielded 210 and 78 articles on "management of subaxial cervical spine injuries" and the role of "SLICS" and "AO Spine" respectively. Keywords "management of traumatic facet locks" were searched and closed reduction, traction, approaches and techniques were studied. "Vertebral artery injury and cervical fracture" exhibited 2,328 references from the last 15 years. The objective was to identify the appropriate diagnostic tests and optimal treatment. Up-to-date information was reviewed, and statements were produced to reach a consensus in 2 separate consensus meetings of World Federation of Neurosurgical Societies (WFNS) Spine Committee. The statements were voted and reached a positive or negative consensus using Delphi method. Based on the most relevant literature, panelists in Moscow consensus meeting conducted in May 2019 drafted the statements, and after a preliminary voting session, the consensus was identified on various statements. Another meeting was conducted at Peshawar in November 2019, where in addition to previous statements, few other statements were discussed and voted. Specific recommendations were then formulated guiding classification, management, locked facets and vertebral artery injuries. This review summarizes the WFNS Spine Committee recommendations on subaxial cervical spine injuries.